2016
DOI: 10.1111/bjet.12479
|View full text |Cite
|
Sign up to set email alerts
|

E‐portfolio evaluation and vocabulary learning: Moving from pedagogy to andragogy

Abstract: Current trends in the field of educational technology indicate a shift in pedagogical assumptions and theoretical frameworks that favor active involvement of self‐directed learners in a constructivist environment. This study probes the influence of electronic portfolio evaluation on vocabulary learning of Iranian university students and the possible implications this influence affords. For this aim, the study recruited 66 students who were randomly assigned to the e‐portfolio group and the traditional assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…E-portfolios are also used to establish professional performance and competency standards that can be found in government licensing programs. Importantly, eportfolios can be self-assessed [39], which allows students to analyze their development and identify strengths and weaknesses. Studies focused on student perception show that learners recognize the benefits of e-portfolio as a learning tool [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-portfolios are also used to establish professional performance and competency standards that can be found in government licensing programs. Importantly, eportfolios can be self-assessed [39], which allows students to analyze their development and identify strengths and weaknesses. Studies focused on student perception show that learners recognize the benefits of e-portfolio as a learning tool [40].…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlation between the expected support and motivation to use an e-portfolio, and feedback and support from peers and educators are important for self-regulated learning [46]. Students also had negative perceptions of the e-portfolio when the requirements were not properly balanced with other coursework [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, researchers have not had access to the type or amount of content that can be produced within e-portfolio spaces, so this is an area that represents what could be a revolutionary approach to exploring language development over time (Cummins & Davesne, 2009, p.856). With growing access to online social media platforms that may be used to document and share experiences, e-portfolio research has more recently gained scholarly attention related to language learning (Barrot, 2016;Cheng & Chau, 2009;Sharifi, Soleimani, & Jafarigohar, 2017;Williams, Chan, & Cheung, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The oldest participant is reported to be 58 years old. However, there is only one study that includes participants of such age [24]. Even though the market for learning foreign languages is considerably vast and there are numerous adults who want or have to learn languages, no studies on these specific age groups were found.…”
Section: Samples and Their Characteristicsmentioning
confidence: 99%
“…There were no investigations on how various types of technology are being used to teach languages to the elderly either. Edmodo [3] WhatsApp [4] Educational game "The Conference Interpreter" [5] Mobile app [6] PDA with a GPS sensor [8] Jigsaw tasks on slides [10] Google Docs, Glogster, NaturalReader [11] OpenSimulator Project-CLILiOP [12] The Content Management System [13] Augmented Reality game [14] Computer game [15] Vine [16] e-glosses [17] e-book [18] My English Vocabulary Assistant mobile edition MyEVA Mobile [19] e-book [21] Video game World of Warcraft [22] Mobile PC learning system [23] Mobile learning system [24] e-portfolio [25] Personal response system EnClicker [26] Analytical Writing Discussion Forum [27] Online discussion forum eLearn [29] Digital annotation tool Hylighter [30] Happy English Learning System [31] Context-aware technologies on PC [32] Augmented Reality [33] Clickers…”
Section: Samples and Their Characteristicsmentioning
confidence: 99%